p53 isoforms, Δ133p53 and p53β, are endogenous regulators of replicative cellular senescence - Fujita, Kaori (2009)
The finite proliferative potential of normal human cells leads to replicative cellular senescence, which is a critical barrier to tumour progression in vivo1–3. We show that human p53 isoforms (Δ133p53 and p53β)4 constitute an endogenous regulatory mechanism for p53-mediated replicative senescence. Induced p53β and diminished Δ133p53 were associated with replicative senescence, but not oncogene-induced senescence, in normal human fibroblasts. The replicatively senescent fibroblasts also expressed increased levels of miR-34a, a p53-induced microRNA5–9, the antisense inhibition of which delayed the onset of replicative senescence. The siRNA-mediated knockdown of endogenous Δ133p53 induced cellular senescence, which was attributed to the regulation of p21(WAF1) and other p53 transcriptional target genes. In overexpression experiments, while p53β cooperated with full-length p53 to accelerate cellular senescence, Δ133p53 repressed miR-34a expression and extended cellular replicative lifespan, providing a functional connection of this microRNA to the p53 isoform-mediated regulation of senescence. The senescence-associated signature of p53 isoform expression (i.e., elevated p53β and reduced Δ133p53) was observed in vivo in colon adenomas with senescent phenotypes10, 11. The increased Δ133p53 and decreased p53β isoform expression found in colon carcinoma may signal an escape from the senescence barrier during the progression from adenoma to carcinoma.